Clinical Outcomes and Identification of Patients With Persistent Penumbral Profiles Beyond 24 Hours From Last Known Well: Analysis From DEFUSE 3. Issue 3 (10th February 2021) - Sarraj, Amrou; Mlynash, Michael; Heit, Jeremy; Pujara, Deep; Lansberg, Maarten; Marks, Michael; Albers, Gregory W.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background and Purpose: DEFUSE 3 (Endovascular Therapy Following Imaging Evaluation for Ischemic Stroke 3) infarct volumes at 24 hours did not significantly differ in the endovascular thrombectomy (EVT) versus medical management (MM) only groups. We hypothesized that this was due to underestimation of the final infarct volume among patients with persistent penumbral tissue 24 hours after randomization that subsequently progressed to infarction. We sought to assess the clinical outcomes in patients with persistent penumbral profile >24 hours from last known well and identify them based on the Persistent Penumbra Index (PPI, time-to-maximum of the residue function >6 s perfusion lesion divided by diffusion-weighted magnetic resonance imaging lesion volume on 24-hour postrandomization imaging). Methods: Patients were stratified into those with a 24-hour postrandomization penumbral (PPI>1) versus a nonpenumbral (PPI≤1) profile. The primary outcome was 90-day–modified Rankin Scale. Results: One hundred eighty-two patients were randomized (EVT: 92, MM: 90). Twenty-four–hour postrandomization time-to-maximum of the residue function and infarct volumes were assessable for 144 (EVT: 75, MM: 69). Infarct volumes did not differ between EVT and MM (median [interquartile range] mL: 35.0 [17.6–81.6] versus 41.0 [25.4–106.2], P =0.185). Thirty-two patients had persistent penumbral profile (PPI>1), of these 29 (91%) received MM. PPI was 0 (0–0.07) for EVT, and 0.77 (0.23–1.79) for MM, P <0.001. Patients with clinical-imaging mismatch (more severe strokes and smaller infarct volumes) were more likely to have persistent penumbral profile (PPI>1; adjusted odds ratio, 1.20 [1.11–1.30] for every 1-point National Institutes of Health Stroke Scale-increment and adjusted odds ratio, 0.977 [0.964–0.990] for every 10 cc smaller infarct volume, P <0.001). Patients with nonpenumbral profile (PPI≤1) had higher odds of achieving functional independence (39% versus 9%; adjusted odds ratio, 9.9[95% CI, 2.3–42.8], P =0.002), a trend towards lower mortality (12% versus 34%, P =0.002; adjusted odds ratio, 0.34 [95% CI, 0.11–1.03], P =0.057) and early clinical improvement (24-hour National Institutes of Health Stroke Scale—decrease ≥8 points or 0–1): 29% vs 9%, P =0.034) which persisted at discharge and 90-day follow-up. For a given volume, patients with PPI≤1 had significantly higher likelihood of functional independence as compared to those with PPI>1. Conclusions: Patients with persistent penumbral profile who have salvageable tissue beyond 24 hours from last known well can be identified by PPI and clinical-imaging mismatch. They have a poor prognosis and may benefit from very late window reperfusion therapies. Clinical trials in these patients are warranted. Registration: URL: https://www.clinicaltrials.gov . Unique identifier: NCT02586415.